SPATIAL AND TEMPORAL VARIABILITY OF CHLOROPHYLL-A IN SURFACE WATERS OF SOUTHERN JAVA-TIMOR SEA DURING THE 2019-2022 TRIPLE-DIP LA NIÃA EVENT - Aldifa Amar, Amaridha
Chlorophyll-a is a green pigment in phytoplanktons that plays a role in the photosynthesis process and is influenced by environmental factors and oceanographic conditions of the water. One of the sea that has high chlorophyll-a variability is the southern waters of Java-Timor Sea which is influenced by the monsoon wind system and the phenomenon of ocean-atmosphere interaction. This study aims to assess the spatial and temporal variability of chlorophyll-a concentration and sea surface temperature (SST) in the southern waters of Java-Timor Sea during the triple-dip La Niña event in 2019-2022. Chlorophyll-a and SST variability were studied based on Aqua MODIS level 3 satellite image data compared with wind speed data from ERA5, rainfall data from CHIRPS, and ONI and DMI data. The relation between chlorophyll-a and SST is explained based on the calculation of correlation. Meanwhile, the influence of triple-dip La Niña is explained by comparing the lowest SST and highest chlorophyll-a at 7 observation points for 3 case scenarios, namely La Niña-IOD(+), La Niña-IOD(-), and triple-dip La Niña. The results showed that chlorophyll-a and SST varied with time, location, and variations in ocean-atmosphere interaction phenomena. Based on location, the waters around the southern Java-Sawu Sea have higher chlorophyll-a concentrations and cooler SST than the southern Sawu Sea-Timor Sea. While based on time, chlorophyll-a is higher and SST is cooler in May-October, and vice versa in November-April. Chlorophyll-a and SST have an inversely proportional rela-tionship with higher chlorophyll-a concentrations and cooler SST in the eastern monsoon period. Chlorophyll-a concentration becomes higher when wind speed is high, SST is cold, and rainfall intensity is low. The results of observations at 7 points showed that chlorophyll-a concentrations ranged from 0.04-4.10 mg/m3 and SST at 23.18- 31.17o C during El Niño 2019, while during triple-dip La Niña 2020-2022 chlorophyll-a concentrations ranged from 0.02-2.36 mg/m3 and SST at 25.80- 31.80oC. The results of the comparison of the highest chlorophyll-a and the lowest SST of the 3 case scenarios explain that it is not the duration but the intensity of La Niña that affects chlorophyll-a and SST